2016
DOI: 10.1155/2016/9823025
|View full text |Cite
|
Sign up to set email alerts
|

The Prosthetic Workflow in the Digital Era

Abstract: The purpose of this retrospective study was to clinically evaluate the benefits of adopting a full digital workflow for the implementation of fixed prosthetic restorations on natural teeth. To evaluate the effectiveness of these protocols, treatment plans were drawn up for 15 patients requiring rehabilitation of one or more natural teeth. All the dental impressions were taken using a Planmeca PlanScan® (Planmeca OY, Helsinki, Finland) intraoral scanner, which provided digital casts on which the restorations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
0
17
0
4
Order By: Relevance
“…Laboratory procedures of fabrication of monolithic zirconia restorations, from beginning to end, include: zirconia ceramic blank/block selection, restoration design, milling the zirconia blank/block, coloring, sintering, polishing and finishing, staining, and glazing the restoration . Zirconia ceramic selection is accomplished according to mechanical, esthetic, and clinical requirements.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Laboratory procedures of fabrication of monolithic zirconia restorations, from beginning to end, include: zirconia ceramic blank/block selection, restoration design, milling the zirconia blank/block, coloring, sintering, polishing and finishing, staining, and glazing the restoration . Zirconia ceramic selection is accomplished according to mechanical, esthetic, and clinical requirements.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…The results of our study were in accordance with many previous studies. (1,5,(11)(12)(13)(14)(15)(16) A previous study concluded that digital impressions create accurate physical models for all-on-four implants rehabilitation, (5) and that x-ray examination revealed a bar -implant connection accuracy. Another study concluded that clinical precision of digital quadrant impression models (I Tero Cadent, Lava COS, Lava true definition, 3 Shape Trios, Trios color, Cerec blue cam and Cerec omnicam) is sufficient to cover broad variety of restorative indications, giving precision within clinically acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…The scanner's camera has a resolution of 600 Â 800 pixels, accuracy of 5.26 + 0.338 mm for single crown and precision (repeatability) of 3.18 + 0.487. It captured the cleft anatomy ( Figure 1) with precision and the files were converted to Standard Tessellation Language (Ciocca et al, 2009;Tordiglione et al, 2016) for the purpose of 3-dimensional (3-D) printing. The files were then interpreted using EXOCAD software (version 2016), which is a CAD software.…”
Section: Methodsmentioning
confidence: 99%
“…This is then attached with a nasal stent (Grayson and Court, 2001; Grayson and Maull 2004) and the appliance is delivered. We have devised a method to fabricate most parts of the NAM plate using digital technology such as intraoral scanners, computer-assisted designing (CAD) technology (Ciocca et al, 2009; Tordiglione et al, 2016), and sophisticated 5-axis milling machine and finally completing the assembly by attaching a nasal stent, which is fabricated separately in the laboratory.…”
Section: Introductionmentioning
confidence: 99%